The Economics of Fiscal Rules and Debt Sustainability - Roel Beetsma (Intereconomics, 2022)
Because they exert cross-border spillover effects, fiscal policies of individual EU member states are a common concern for the entire EU.
Keywords: E62; H6; 330; Finanzpolitik; Öffentliche Schulden; EU-Staaten